Designing a Model of Waste Management for Sustainable Rural Development (Case study: villages of Gilan Province) - Mortez Hazrati; Sevda Sheikhi Lisar; Mohammad Taghipour (Recent Trends in Social Studies, 2024)
Paying attention to waste management is one of the most important tasks defined for urban and rural officials around the world. These days, every small and large city or every village and hamlet you visit is faced with a problem called waste and waste management. This is all the more important when we know that most of this waste comes from seasonal streams and rivers; On the other hand, the mismanagement of this waste affects the social security and health of the people and is polluted. Because all this leachate and waste pollution is discharged into reservoirs and groundwater and surface water sources. Currently in Iran, 80% of the total waste management costs are related to collection, 60% of which is spent on workers' wages. This is important because a small improvement in collection operations can have a significant impact on reducing overall costs. The growth of urban population and increase in migration to cities, has led to uncontrollable development of urban areas, reducing the level of human welfare, achieving suburbanization and the emergence of many problems for various urban managers, especially in developing countries. Urban planners are worried about it, and it has given rise to a significant investigation involving managers, planners, and legislators.
Keywords: Delphi method; Pattern design; Waste management; sustainable rural development; urban planners